THE INFERENCE METHOD OF WHEEL LOAD BASED ON THE ACCELERATION OF AXLE HEAD - ZHENG SongLin; GUO ZhengXiang; FENG JinZhi; FANG Jin; SHEN YongFeng (Jixie qiangdu)
A new load spectrum measuring method which can instead of the six-component measuring wheel was carried out in this paper. Through analysis the signal time-domain,a linear model between the axle head and the wheel was established. By using real-time signal transformation and mathematical statistics method,the collected load spectrum of vertical wheel load and the vertical acceleration of the axle head,an inference model were analyzed and discussed between the axle head and the wheel.The analysis method was validated by a reality car test. The wheel vertical load and axle head vertical acceleration calibrated was conducted by four pillars road simulation test bed,and the skid pad load spectrum was acquisitioned. Compared with the load spectrum of collected wheel vertical force and inference load spectrum of wheel vertical force,the correctness of model was verified. Finally,the results indicated that this inference method can replace the six-component measuring wheel for road load spectrum acquisition.